Perancangan storyboard animasi pendek 2D guna mengenalkan Kerajaan Pagaruyung - Latifah Rasyada; Muhammad Iskandar; Angelia Lionardi (KalaTanda, 2021)
Rumah Gadang is a traditional house of the Minangkabau tribe. Traditional houses are a wealth of objects that can be used as tourism objects. The famous Rumah Gadang Istano Basa Pagaruyung in West Sumatra was formerly the center of government of the Pagaruyung kingdom and became the residence of the royal family. Now this Gadang House is a cultural heritage asset for the Minangkabau tribe and has changed its function as a museum. It's a shame that the prestige of the museum, which is full of history, is getting less and less well-known, as can be seen from visits that only make it a location for selfies without going into and studying the collections contained in the museum. Therefore, a storyboard will be made that introduces the Kingdom of Pagaruyung. Qualitative method research was conducted to find visual ideas that could be adopted as the basis for the design. Data collection used interviews and direct observation. The findings were also strengthened by a literature study targeting youth in West Sumatra. This design is expected to continue into an animated film. Keywords: Pagaruyung Kingdom, Istano Basa Pagaruyung, Storyboard animation